Nutritional therapy in Chronic Kidney Disease - Antonio Santoro; Dino Gibertoni; Andrea Ambrosini; Ciro Esposito; Gianvincenzo Melfa; Federico Alberici; Giuseppe Vanacore (AboutScience Srl, 2024)
Dietary-Nutritional Therapy (DNT) is an essential component of the conservative management of patients with chronic kidney disease (CKD) as it helps maintain optimal nutritional status, prevent and/or correct symptoms and complications of CKD. Moreover, it allows adherent patients to delay the onset of dialysis, leading to improved quality of life and cost savings for both patients and the community. Through a survey, we aimed to evaluate how personalized diets were assessed, administered, and experienced by CKD patients. A questionnaire was administered to 180 patients from 4 nephrology Centers in Lombardy, (Italy,) regarding their CKD and nutritional therapy. 73% of patients received dietary prescriptions. In 40% of cases, dietary prescriptions were administered in dedicated clinics and were valued as much as pharmacological ones. Most diets prescribed were low-protein (0.8g protein per kg of body weight), although some included very low protein diets supplemented with keto analogs. Unfortunately, post-initial prescription, monitoring adherence to nutritional therapy is not particularly frequent. In conclusion, our survey suggests that while patients in different Nephrology Centers receive proper dietary prescriptions and follow-ups, there are areas for improvement with positive implications for CKD progression and delaying dialysis therapy.